Cryptocurrencies and blockchain technology applications - Shrivastava, Gulshan, 1987-; Le, Dac-Nhuong, 1983-; Sharma, Kavita (John Wiley & Sons, Inc., 2020)
"As we enter the Industrial Revolution 4.0, demands for an increasing degree of trust and privacy protection continue to be voiced. The development of blockchain technology is very important because it can help frictionless and transparent financial transactions and improve the business experience, which in turn has far-reaching effects for economic, psychological, educational and organizational improvements in the way we work, teach, learn and care for ourselves and each other. Blockchain is an eccentric technology, but at the same time, the least understood and most disruptive technology of the day. This book covers the latest technologies of cryptocurrencies and blockchain technology and their applications. This book discusses the blockchain and cryptocurrencies related issues and also explains how to provide the security differently through an algorithm, framework, approaches, techniques and mechanisms. A comprehensive understanding of what blockchain is and how it works, as well as insights into how it will affect the future of your organization and industry as a whole and how to integrate blockchain technology into your business strategy. In addition, the book explores the blockchain and its with other technologies like Internet of Things, big data and artificial intelligence, etc."- Resumé vydavatel
Keywords: virtuální měna; blockchain (technologie); virtual money; blockchain (technology); elektronické knihy; kolektivní monografie; electronic books; collective monographs